Effect of Roxadustat on the Pharmacokinetics of Simvastatin, Rosuvastatin, and Atorvastatin in Healthy Subjects: Results From 3 Phase 1, Open‐Label, 1‐Sequence, Crossover Studies. Issue 4 (19th February 2022) - Groenendaal‐van de Meent, Dorien; den Adel, Martin; Kerbusch, Virginie; van Dijk, Jan; Shibata, Tomohisa; Kato, Kota; Schaddelee, Marloes
Abstract: Roxadustat inhibits breast cancer resistance protein and organic anion transporting polypeptide 1B1, which can affect coadministered statin concentrations. Three open‐label, 1‐sequence crossover phase 1 studies in healthy subjects were conducted to assess effects from steady‐state 200‐mg roxadustat on pharmacokinetics and tolerability of 40‐mg simvastatin (CL‐0537 and CL‐0541), 40‐mg atorvastatin (CL‐0538), or 10‐mg rosuvastatin (CL‐0537). Statins were dosed concomitantly with roxadustat in 28 (CL‐0537) and 24 (CL‐0538) healthy subjects, resulting in increases of maximum plasma concentration (Cmax ) and area under the plasma concentration–time curve from the time of dosing extrapolated to infinity (AUCinf ) 1.87‐ and 1.75‐fold for simvastatin, 2.76‐ and 1.85‐fold for simvastatin acid, 4.47‐ and 2.93‐fold for rosuvastatin, and 1.34‐ and 1.96‐fold for atorvastatin, respectively. Additionally, simvastatin dosed 2 hours before, and 4 and 10 hours after roxadustat in 28 (CL‐0541) healthy subjects, resulted in increases of Cmax and AUCinf 2.32‐ to 3.10‐fold and 1.56‐ to 1.74‐fold for simvastatin and 2.34‐ to 5.98‐fold and 1.89‐ to 3.42‐fold for simvastatin acid, respectively. These increases were not attenuated by time‐separated statin dosing. No clinically relevant differences were observed for terminal elimination half‐life. Concomitant 200‐mg roxadustat and a statin was generally well tolerated during the study period. Roxadustat effects on statin Cmax and AUCinf were statin and administration time dependent. When coadministered with roxadustat, statin‐associated adverse reactions and the need for statin dose reduction should be evaluated.